Intestinal Complication With Myxomatous Mitral Valve Diseases in Chihuahuas - Araki, R.; Iwanaga, K.; Ueda, Kazunori; Isaka, M. (Frontiers in Veterinary Science, 2021)
The effects of cardiac disease on the intestine have been reported in humans but not in dogs. We investigated the effects of myxomatous mitral valve disease (MMVD), which is capable of causing congestion and tissue hypoperfusion, on the intestine in Chihuahuas, a breed frequently encountered in clinical practice as the preferred breed for MMVD. In this study, 69 Chihuahuas were divided into four groups based on echocardiography and chest radiography: 19 healthy Chihuahuas (H) and 50 Chihuahuas with MMVD classified according to the ACVIM consensus (stage B1, B2, C/D). In all the cases, serum intestinal fatty acid-binding protein (I-FABP) and D/L-lactate concentrations, markers of intestinal mucosal injury, were measured. I-FABP was significantly higher in stage C/D Chihuahuas than in other groups (p < 0.05), and stage B2 was significantly higher than H (p < 0.05). D-lactate was significantly increased in stages B2 and C/D compared to H and stage B1 (p < 0.05). L-lactate was significantly higher in stage C/D Chihuahuas than in any other group (p < 0.05), and stage B2 was significantly higher than that in H and stage B1 (p < 0.05). Intestinal mucosal injury risk was significantly higher in Chihuahuas with heart failure due to MMVD, suggesting that the risk could increase with worsening heart disease. This is the first study to investigate the intestinal complications of MMVD, and further investigations a needed in the future.